2010
DOI: 10.5001/omj.2010.24
|View full text |Cite
|
Sign up to set email alerts
|

Colon Targeted Drug Delivery Systems: A Review on Primary and Novel Approaches

Abstract: The colon is a site where both local and systemic delivery of drugs can take place. Local delivery allows topical treatment of inflammatory bowel disease. However, treatment can be made effective if the drugs can be targeted directly into the colon, thereby reducing the systemic side effects. This review, mainly compares the primary approaches for CDDS (Colon Specific Drug Delivery) namely prodrugs, pH and time dependent systems, and microbially triggered systems, which achieved limited success and had limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
190
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(190 citation statements)
references
References 64 publications
0
190
0
Order By: Relevance
“…The pH of GIT changes and is always varying, but these three pH values have been used in many studies conducting preliminary and in vitro release tests to mimic the pH conditions of the GIT. A solution at pH 1.2 represents gastric fluid in the stomach, while buffer solutions at pH 6.8 and pH 7.4 simulate the jejunal region of small intestine and the ileum segment, respectively [20,23,39].…”
Section: Loading and In Vitro Release Kinetics Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The pH of GIT changes and is always varying, but these three pH values have been used in many studies conducting preliminary and in vitro release tests to mimic the pH conditions of the GIT. A solution at pH 1.2 represents gastric fluid in the stomach, while buffer solutions at pH 6.8 and pH 7.4 simulate the jejunal region of small intestine and the ileum segment, respectively [20,23,39].…”
Section: Loading and In Vitro Release Kinetics Studymentioning
confidence: 99%
“…The release of EGCG was done in three pH levels of solution, such as 1.2, 6.8 and 7.4, to act as GIT fluids, specifically simulating gastric fluid, the jejunal region of small intestine and the ileum segment, respectively [23]. Approximately, 0.1 M HCl was used to make pH 1.2, while PBS was used to for pH 6.8 and 7.4.…”
Section: In Vitro Egcg Release Kineticsmentioning
confidence: 99%
“…Therefore, chitosan derivatives with enhanced solubility at basic and neutral pH are essential. [12][13][14][15] It has been shown that TMC, a quaternary derivative of chitosan, enhances penetration and opens epithelial tight junctions in the environments with basic and neutral pH. 14 The gastric enzymes and acidic conditions pose challenges to the oral administration of vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Inside the human colon, numerous bacteria secrete enzymes that break down the polymer backbone, resulting in decrease in its molecular weight, thus losing their mechanical strength and ending up with the release of drug entity. Besides pectin, CS is also able to shield drugs from harsh stomach and small intestine environment [33]. A successful colon drug delivery requires the triggering mechanism in the delivery system that only responds to the physiological conditions particular to the colon [34].…”
Section: In Vitro Drugmentioning
confidence: 99%